2012
DOI: 10.5539/ass.v8n2p34
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Perception Differences among International Students and Local Students: A Case Study of Australia and New Zealand

Abstract: This qualitative study was designed to gather information, using focus groups, about Asian international students' experiences and attitudes toward Australian-New Zealanders, to identify the sources of these attitudes, and to discover methods that could address negative attitudes that Asian students might have towards Australian-New Zealanders students. Data were collected from 200 respondents by using simple random technique at the ratio of 100 respondents each (Asian, and Australian-New Zealander students). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Particularly relevant to Asian‐born international students' intercultural evaluation is that some might hold prejudicial attitudes before arriving in Australia, as emerging research suggests (e.g. Latif et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly relevant to Asian‐born international students' intercultural evaluation is that some might hold prejudicial attitudes before arriving in Australia, as emerging research suggests (e.g. Latif et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested a noticeable social divide between international and domestic students, with generally low levels of intergroup interactions and particularly of friendships (Latif, Bhatti, Maitlo, Nazar, & Shaikh, ; Rosenthal, Russell, & Thomson, ). Furthermore, there have been incidents of international students being the target of racially motivated discrimination from domestic students in Australia (Barron, ) and even victims of crime from members of the general community in Western countries all over the world (Nyland, Forbes‐Mewett, & Marginson, ).…”
mentioning
confidence: 99%
“…Students were separated into two groups -domestic and international students. This purposeful segmentation follows previous studies which have grouped international students together to make them feel comfortable and more at ease to share their thoughts and opinions among their peers (Latif et al, 2012;Hynes et al, 2011). Each focus group consisted of seven full time students and lasted an average of 1 hour in duration.…”
Section: Methodsmentioning
confidence: 99%